Bernt Carlsson address at the National Press Club on 14 October 1981 - Carlsson, Bernt; National Press Club (Australia) (1981)
Mr. Carlsson spoke on the needs of Socialist International (the oldest, largest political organisation); the arms race and control of disarmament; economic policy; the planning of the 1983 Socialist International Congress, the structure of the organisation.
Also available online
Bernt Carlsson was Secretary-General Socialist International at the time of this recording.
Timed summary (5 p.).
Keywords: Carlsson, Bernt; Socialist International; Arms race; Disarmament